Studying diesel oil biodegradation of the bacterial strain BTLD5 isolated from industrial wastewater - Ngoc Mai, Cung Thi; Linh, Nguyen Thuy; Bac, Nguyen Van; Thanh, Vu Thi; Minh, Nghiem Ngoc (Academia Journal of Biology, 2012)
The bacterial strain BTLD5 was isolated from wastewater of Tu Liem industrial zone. This strain had round and smooth colony with 2 mm diameter. The cell morphology of the strain BTLD5 was observed under the Scaning Electron Microcopy showed that it was a short rod with 0.73 - 0.91 mm in wide and 1 - 1.8 mm in length. The strain BTLD5 is able to utilize diesel oil as sole energy and carbon sources. After 7 days in shake cultivation, 89.3% adding oil was removed. The nucleotide sequence of the 16S rRNA gene had been used for taxonomy of the strain BTLD5. The result of the amplification of the nucleotide sequence with the primer 27f/1492r indicated that the strain BTLD5 had high homology with the species of the genus Pseudomonas and was close to the Pseudomonas aeruginosa strain (X06684). Based on the morphology and the 16S rRNA gene nucleotide sequence, this strain belong to genus Pseudomonas and named Pseudomonas sp. BTLD5. The nucleotide sequence of the 16S rRNA gene was deposited in the NCBI genbank database with assession number JF750922.